Nonlinearities in the Relationship Between Oil Price Changes and Movements in the Norwegian Krone - Saskia ter Ellen (Norges Bank, 2016)
Anecdotal evidence as well as previous empirical analysis indicates that the relation between oil price changes and movements in the Norwegian krone is not stable over time. We can observe that there is no or only a weakly significant correlation between oil price changes and Norwegian krone depreciation in some periods, but a strong correlation in other periods. This memo proposes some explanations for these nonlinearities and summarizes the results of empirical tests conducted to investigate the nonlinearities in the oil price-Norwegian krone relation. It is found that the Norwegian krone reacts stronger to oil price changes when these are larger than average, and that the most relevant threshold level for the 2014 price drop was USD 75.
hdl:11250/2506529
Keywords: 330